Framing the Poor: Media Coverage and U.S. Poverty Policy, 1960–2008. Issue 1 (21st February 2013) - Rose, Max; Baumgartner, Frank R.
<x xml:space="preserve">Abstract</x> Public policy toward the poor has shifted from an initial optimism during the War on Poverty to an ever‐increasing pessimism. Media discussion of poverty has shifted from arguments that focus on the structural causes of poverty or the social costs of having large numbers of poor to portrayals of the poor as cheaters and chiselers and of welfare programs doing more harm than good. As the frames have shifted, policies have followed. We demonstrate these trends with new indicators of the depth of poverty, the generosity of the government response, and media framing of the poor for the period of 1960–2008. We present a simple statistical model that explains poverty spending by the severity of the problem, gross domestic product, and media coverage. We then create a new measure of the relative generosity of U.S. government policy toward the poor and show that it is highly related to the content of newspaper stories. The portrayal of the poor as either deserving or lazy drives public policy.